PERANCANGAN SISTEM INFORMASI ADMINISTRASI KEUANGAN DESA BERBASIS VISUAL STUDIO DI KECAMATAN TANJUNGSIANG - Susilawati; Muthmainnah; Abdussalaam, Falaah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Tanjungsiang District, located in Subang Regency, West Java, is one of 30 sub-districts consisting of 10 villages. This study identified problems related to manual financial management practices in these villages, leading to a lot of inaccurate and erroneous financial information. Therefore, this study focuses on designing a financial management information system for villages in Tanjungsiang district. The research method used is a qualitative method including direct observation, interviews, discussions with Tanjungsiang District Office staff and data collection from various sources such as books, scientific articles, and other publications. online source. The development methodology used is the Waterfall model, which includes analysis, design, implementation, testing, and maintenance phases, with support from Unified Modeling Language (UML). Microsoft Visual Studio 2010 is used as the development platform, while Microsoft Access 2019 is used for database hosting. The expected result of this research is an accurate and reliable financial recording system that facilitates revenue and expenditure management, with an easy-to-use interface that is easy to understand and use for users.